Resin modified glass ionomer cement as an alternative restoration material: Resin modified glass ionomer cement sebagai bahan restorasi alternatif - Dewi, Maya Sari; Nugraha, Putu Yetty (Makassar Dental Journal PDGI Makassar, 2024)
Oral health is important in today's modern world, as it allows individuals to eat, speak and socialise comfortably. But sometimes this condition is difficult to achieve, because the incidence of caries is still quite high. Dental caries is an infectious disease of the hard tissues of the teeth, namely enamel, dentin and cementum. If dental caries is not treated, it can continue to the supporting tissues of the teeth. Dental restoration materials help to reconstruct and repair dental hard tissues. To improve the physical pro-perties and reduce the water sensitivity of conventional materials, resin-modified glass ionomer cements (RMGIC) were deve-loped, which are restoration materials that combine the properties of conventional glass ionomer cements with composite resins. Several studies have shown that the amount of fluorine ions released by hybrid ionomers in RMGIC is greater than other res-toration materials such as composite resins and composites, making RMGIC an option.